Rare Case of Sino-Nasal Rosai Dorfman Disease - Anushree BajaJ; Shruti Khandagale; vikrant Vaze (Bengal Journal of Otolaryngology and Head Neck Surgery, 2023)
ABSTRACT : Introduction: Rosai-Dorfman disease (RDD) is a very rare nonneoplastic lymphoproliferative disease with unknown etiology and pathogenesis. It was originally described as sinus histiocytosis with massive lymphadenopathy(SHML). Approximately 43% of Rosai-Dorfman disease show extra nodal involvement wherein the possible sites are skin, CNS, ear, orbit and rarely nose and paranasal sinuses. Definitive diagnosis can be performed by histopathological examination, which shows emperipolesis. The sinus histiocytes are strongly reactive for S-100 protein and CD68, but negative for CD1a. Case Report: The current study presents the case of a 29 year old male patient who had complaints of nasal obstruction since 5 months. Diagnostic Nasal Endoscopy showed mass completely filling both nasal cavities. Histopathological examination concluded the diagnosis of Rosai-Dorfman Disease and Immunohistochemistry (IHC) stained positive for S-100 and CD68, while negative for CD1a, of the surgical specimen after surgical excision by Functional Endoscopic Sinus Surgery. Follow up was done after a week, monthly for 6 months and a year for recurrence Discussion: Extranodal RDD, although rarely seen, should be considered in nasal cavity. Even though there is no ideal protocol in the treatment, surgical excision should be considered if there is a functional disorder.